Effects of food pH on the feeding response and growth performance of juvenile marble goby, oxyeleotris marmorata - Teoh, Chui Fen (2018)
Marble goby (Oxyeleotris marmorata ) is a freshwater fish species with high commercial value that being widely cultured in Southeast Asia. In hatchery, this fish generally reject formulated feed, and there is still no species-specific commercial feed for this fish. Previous studies found that amino acids, nucleotide and nucleosides were effective feeding stimulant to improve the feed intake and weaning of this fish. However, those taste substances are expensive. Alternate methods with the lower cost is therefore necessary. Fish can sense sour taste, and their taste preference for food pH is speciesspecific. Therefore, manipulating food pH can be practiced to promote feed intake in fish. This study was aimed to determine the preferable food pH of O. marmorata and their feeding and growth performance when fed with the pH-manipulated diets. Totally 3 experiments were done in this study. In Experiment I, behavioural assay was conducted to determine the food pH preferable by the O. marmorata . Eight pH levels of agar gel pellets (pH 2.4, 3.0, 3.2, 3.4, 4.1, 4.9, 5.1, and 5.9) were tested on 50 individuals (1 fish=1 replicates; TL, 6.6-7.0 cm). Ingestion ratio (IR=number of ingested pellet/50) of each treatment was calculated, and significant differences (P <0.05) among treatments was determined using binomial test. A strong negative relationship (r = - 0.952; P <0.01) was found between the IR and pH level of the agar gel pellets. The IR of pH 2.4 agar gel pellet was the highest (94%) with significant different (P <0.05) to the others, except pH 3.0. These results proved that O. marmorata preferred acidic foods, and the most preferred one was at pH 2.4 to 3.0. In Experiment II, the feeding performance of O. marmorata to the acidified diets (AD) was evaluated. Five fish mealbased diets supplemented with HCl at different pH levels were prepared; the dietary treatments included the control (pH 6.0), AD 5.3, AD 4.3, AD 3.2 and AD 2.5. Each of these diets were fed to 10 individuals (1 fish=1 replicate; 10 fish/treatment; TL, 5.29±0.29 cm) wild caught O. marmorata for 20 day. Five pieces of pellets were given to each fish around 1600h, and the number of uneaten pellet was counted at 2000h. At the end of experiment, the daily IR of fish fed AD 2.5 and AD 3.2 were significantly (P <0.05) higher than control (IR = 0 – 0.06). The successfully weaned fish (60%) and percentage of fish with “Good” feeding performance of fish (70%) fed with AD 2.5 were the highest, and were significantly (P <0.05) higher than other treatments. These findings recommended that AD 2.5 can be used as the weaning diet for the O. marmorata . In Experiment III, feeding trials were conducted to determine the growth performance of juvenile O. marmorata fed with the AD. Five experimental diets (same as Experiment II) were prepared. Each diet was fed to triplicate tanks of wild-caught O. marmorata (19 fish/ tank; TL, 4.72±0.46 cm) for 8 weeks. At week 4, the control, AD 5.3, and AD 4.3 treatments were terminated due to the extremely poor total feed intake (TFI, 0 – 0.05 g) and weight gain (WG, -15.3 to -16.9%). The AD 3.2 and AD 2.5 treatments were continued until week 8. Fish fed with the AD 3.2 showed significantly higher (P <0.05) total feed intake (0.98 g) than those fed with the AD 2.5 (0.73 g). Second trial was done to assess the long term effects of AD for another 7 weeks. Thirty fish were randomly selected from each of AD 3.2 and AD 2.5 treatments and each fish was stocked in a 7 L aquaria to eliminate the territorial behaviour as observed in the first trial (1 fish=1 replicate; 30 replicate/treatment). At the end of experiment, fish fed with the AD 3.2 attained significantly higher (P <0.05) WG (34%) than the AD 2.5 (13%). No significant difference (P >0.05) was found in the TFI (1.22g, 1.08 g) and survival (96.5–100%). However, the WG results from the present study was very low compared to the WG of fish fed with the fish meal-based control diet that available from literature. The AD 3.2 hence was not recommended for long term feeding but it can be used to develop a shortterm weaning protocol for O. marmorata.